Shared Microbial Taxa Respond Predictably to Cyclic Time-Varying Oxygen Limitation in Two Disparate Soils - Hall, Steven J.; Huang, Wenjuan; Napieralski, Stephanie A.; Roden, Eric (Frontiers in Microbiology, 2022)
Periodic oxygen (O2) limitation in humid terrestrial soils likely influences microbial composition, but whether communities share similar responses in disparate environments remains unclear. To test if specific microbial taxa share consistent responses to anoxia in radically different soils, we incubated a rainforest Oxisol and cropland Mollisol under cyclic, time-varying anoxic/oxic cycles in the laboratory. Both soils are known to experience anoxic periods of days to weeks under field conditions; our incubation treatments consisted of anoxic periods of 0, 2, 4, 8, or 12 d followed by 4 d of oxic conditions, repeated for a total of 384 d. Taxa measured by 16S rRNA gene sequences after 48 d and 384 d of experimental treatments varied strongly with increasing anoxic period duration, and responses to anoxia often differed between soils at multiple taxonomic levels. Only 19% of the 30,356 operational taxonomic units (OTUs) occurred in both soils, and most OTUs did not respond consistently to O2 treatments. However, the OTUs present in both soils were disproportionally abundant, comprising 50% of sequences, and they often had a similar response to anoxic period duration in both soils (P < 0.0001). Overall, 67 OTUs, 36 families, 15 orders, 10 classes, and two phyla had significant and directionally consistent (positive or negative) responses to anoxic period duration in both soils. Prominent OTUs and taxonomic groups increasing with anoxic period duration in both soils included actinomycetes (Micromonosporaceae), numerous Ruminococcaceae, possible metal reducers (Anaeromyxobacter) or oxidizers (Candidatus Koribacter), methanogens (Methanomicrobia), and methanotrophs (Methylocystaceae). OTUs decreasing with anoxic duration in both soils included nitrifiers (Nitrospira) and ubiquitous unidentified Bradyrhizobiaceae and Micromonosporaceae. Even within the same genus, different OTUs occasionally showed strong positive or negative responses to anoxic duration (e.g., Dactylosporangium in the Actinobacteria), highlighting a potential for adaptation or niche partitioning in variable-O2 environments. Overall, brief anoxic periods impacted the abundance of certain microbial taxa in predictable ways, suggesting that microbial community data may partially reflect and integrate spatiotemporal differences in O2 availability within and among soils.